(untitled) (La Universidad, 2017)
Rodríguez Ruiz fue reconocido como jurista y escritor costumbrista. Fue decano de las facultades de Economía y Humanidades. También fungió como presidente del Consejo Superior Centroamericano (CSUCA). Por su novela Jaraguá es considerado una de las grandes voces de la narrativa hispanoamericana del siglo XX. El cuento que se transcribe a continuación fue publicado originalmente en la revista La Universidad. Abstract He graduated as a Doctor of Laws from the University of El Salvador, Napoleon Rodriguez Ruiz was recognized as a jurist and writer of manners. He was dean of the faculties of Economics and Humanities. He also served as president of the Central Council (CSUCA). For his novel Jaraguá is considered one of the great voices of the twentieth century Latin American narrative. The story is transcribed below was originally published in The University.